He/she/they : how we talk about gender and why it matters - Bailar, Schuyler (Hachette Go, 2023)
"Just a few years ago, Schuyler Bailar rose to national and international prominence when he became the first openly transgender athlete to compete on an NCAA Division 1 team in any sport. A top high school prospect, Schuyler had been recruited by Harvard for the women's team, but after taking a gap year to address mental health and ultimately to transition, Schuyler swam instead for Harvard's men's team. Since then, Schuyler has become a go to expert on gender identity for the media and has given hundreds of talks on gender literacy and inclusion. But at the same time, Supreme Court Justice nominee Ketanji Brown Jackson was asked in her confirmation hearing to define the word "woman," a seemingly simple question that in that particular arena was too politically charged for her to answer. Meanwhile, anti-gay and anti-trans legislation in Florida and Texas shows that trans rights are under attack. Transgender suicides are up, transgender hotlines are buzzing, and the only thing that is certain is this: America is long overdue for a reckoning with gender. He/She/They uses storytelling and the art of conversation to give us the fundamental language and context of gender so that we can meet people where they are and pave the way to understanding, acceptance, and inclusion. As a transgender man, inclusion advocate, and LGBTQ educator, Schuyler Bailar is more than familiar with the myriad questions that come up. In He/She/They, he addresses them head on, such as why being transgender is not a choice, why pronouns are important, and what is biological sex. But this book is more than a book on allyship; many of Schuyler's vast followers come to him for support; one of his most popular reels is speaking to a young trans person who asks, "does it get better?" Schuyler speaks to everyone, no matter where they are. In the same way that So You Want to Talk About Race defined the conversation about race in American, He/She/They is an essential, urgent, and, as Schuyler points out, potentially life-saving book that will change the conversation about gender identity and how we talk about it, moving us toward a more equitable future"--